Malay Grammar for ACADEMICS and PROFESSIONALS - Nik Safiah Karim (Dewan Bahasa dan Pustaka, Kementerian Pendidikan Malaysia, 1995)
This book is written with an emphasis on Malay grammar as a reference point for academics and professionals when they write in the national language. Its main purpose is to provide a brief decsription of the various aspects of Malay grammar with examples of the usage